The Influence of Factors Affecting Safety Performance Among Oil and Gas Offshore Workers With Rosters Schedule: The Mediation Role of Safety Climate. - Nico Nainggolan; Erfa Fatoni D Putra; Rida Zuraida (Syntax Idea)
Oil and gas industry is an industry that has activities with a high level of risk both related to personal safety and process safety. Failure to maintain the safety aspect of the company can have a negative impact on financial, reputation and even a negative consequences from government. In maintaining company performance related to safety, each oil and gas company sets safety performance standards which are included in the company's performance targets. There are several factors that influence safety performance. Therefore this study aims to examine the factors that influence safety performance by mediating safety climate in the Indonesian oil and gas industry. Data was collected using a questionnaire which was distributed to 420 oil and gas field workers and analyzed using Structural Equation Modeling using Smart PLS 4 with 13 hypotheses. The results showed that the factors that had a significant direct effect on safety performance were safety climate and safety culture, while those that had an indirect effect were safety climate, mental health and safety culture. companies can improve safety performance by strengthening the factors that are significantly influential: safety climate, safety culture, mental health and safety behavior.